Analisis Implementasi Sistem Kinerja Anggaran Pada Bagian Umum Secretariat Daerah Kabupaten Batu Bara - Agnes Angelia; Maksum Syahri Lubis; Budi Hartono (Universitas Medan Area, 2022)
The purpose of this study was to analyze the implementation and obstacles in the budget performance system at the General Section of the Regional Secretariat of Batu Bara Regency. The research method used is a qualitative method. The reason for using this qualitative method is because the problem is not clear, holistic, complex, dynamic, and full of meaning so that data on certain social situations is not possible. Implementation of the Budget Performance System in the General Section of the Regional Secretariat of Batu Bara Regency in terms of communication, has been able to communicate with the parties involved. In terms of Human Resources, it is still not optimal in carrying out the budget performance system. In terms of disposition, SKPD has been able to give a good attitude towards all offices. In terms of the Bureaucratic Structure, it still shows that it is less than optimal in budgeting. The obstacle is that the knowledge of SKPD is still not optimal in carrying out budget preparation, so that mature human resources are needed to really understand budget preparation for the smooth running of a good government. The SKPD's lack of understanding of the applicable laws and regulations and the lack of commitment to implement them have made the implementation of the budget performance system not run well.